The complete mitochondrial genome of the Gray's grenadier anchovy Coilia grayii (Teleostei, Engraulidae). (2nd January 2016) - Li, Qiang; Wu, Xiaorui; Shu, Hu; Yang, Huaqiang; Yang, Lidong; Yue, Lei
Abstract: In this paper, the complete mitochondrial DNA (mtDNA) sequence of Coilia grayii was determined. The mitochondrial genome was 16, 851 bp in length, including 13 protein-coding genes, 2 ribosomal RNAs (rRNAs), 22 transfer RNAs (tRNAs) and a non-coding control region as those found in other vertebrates, with the gene identical to that of typical vertebrates. The overall base composition of the heavy strand were 26.09% of A, 31.14% of T, 15.58% of C and 27.19% of G, with a slight AT bias of 57.23%. With the exception of ND6 and eight tRNA genes, all other mitochondrial genes were encoded on the heavy strand.